Aerodynamic Characteristics of the Combustion Process of Sawdust in a Vortex Furnace with Counter-Swirling Flows - Dzhyoiev R.L.; Redko A.A.; Redko I.A.; Pivnenko Yu.A.; Burda Yu.A.; Gvozdetskii A.V.; Alforov S.A. (Problems of the Regional Energetics, 2021)
The aim of this work is to study the working processes of burning the low-quality fuels, namely, the saw dust in the swirling-type furnaces with an opposite twisted motion of the air. The goal was achieved using the physical and mathematical modeling of the flows interaction. The article presented the results of numerical study of aerodynamic characteristics of burning the saw dust in the swirling-type furnace with the opposite twisted air flows. For the research, the facility was used for the saw dust burning with the air supply into the lower and upper zones of burning. The most essential result of the work was modeling of the working process at the ratio of the flows of the primary air and secondary air without the fuel admixture, equal to 0.2. The tangential rate of the flow changed according to the horizontal sections from 3-5 m/s to 40-42 m/s and with respect to the furnace height from 51 m/s to 30 m/s. The average angular rate of the mixture changed relatively the furnace height in the ranges of 171-500 l/s to 100—300 l/s. The significance of the results obtained consists in determination of the possibility of increasing the efficiency of the work of the furnace facilities at the expense of the introduction of the primary and secondary air flows. In this situation, the optimal ratio of consumptions of primary and secondary air was 0.2. Thus, in this work the consumption of primary air was 1.285 kg/s, the consumption of the secondary air was 0.255 kg/s.